Calcium phosphate titanium aluminum lithium as well as preparation method and application thereof

By preparing lithium calcium titanium aluminum phosphate material with high density and high ionic conductivity, the problem of low ionic conductivity of existing lithium titanium aluminum phosphate has been solved, thereby improving the stability and electrical performance of solid-state batteries.

CN120922839APending Publication Date: 2025-11-11SHENZHEN CAPCHEM TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410569120.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing lithium titanium aluminum phosphate materials have low ionic conductivity, and doping elements reduce their density, hindering their commercialization.

Method used

A method for preparing lithium calcium titanium aluminum phosphate was adopted, which involves wet ball milling, staged sintering and tableting to form a lithium calcium titanium aluminum phosphate material with high density and high ionic conductivity.

Benefits of technology

This improved the density and ionic conductivity of lithium calcium titanium aluminum phosphate, thereby enhancing the stability and electrical performance of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120922839A_ABST
    Figure CN120922839A_ABST
Patent Text Reader

Abstract

In order to solve the problems that the density of lithium titanium aluminum phosphate can be reduced and the ionic conductivity is low due to doping of some elements in the prior art, the invention provides lithium titanium aluminum phosphate as well as a preparation method and application thereof. The calcium phosphate titanium aluminum lithium has the chemical composition represented by the following general formula (1): Li < 1.3 + x > Al < 0.3-x > Ca < x > Ti < 1.7 > (PO4) 3 (1), wherein x is more than 0 and less than 0.2. The lithium titanium aluminum calcium phosphate provided by the invention has high density and high ionic conductivity, and when the lithium titanium aluminum calcium phosphate is applied to a solid-state battery, the lithium titanium aluminum calcium phosphate has high density and ionic conductivity as a solid-state electrolyte material, the stability of the battery is improved, and the electrical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of secondary battery technology, specifically relating to a lithium calcium titanium aluminum phosphate, its preparation method, and its application. Background Technology

[0002] Currently, the country is vigorously developing new energy vehicles. Although lithium batteries have made rapid progress, liquid batteries have inherent safety issues, easily leading to battery combustion or even explosions due to leakage, which deters people from purchasing new energy vehicles. Based on these problems, solid-state electrolyte materials have been developed, including polymer and inorganic categories. Among them, lithium aluminum titanium phosphate (LATP) is a classic solid-state electrolyte material system with good stability; however, its relatively low ionic conductivity seriously hinders its commercialization. Currently, researchers are using doping modification methods to improve ionic conductivity, but it has been found that doping with certain elements reduces the density of lithium aluminum titanium phosphate, thus preventing its ionic conductivity from reaching the expected level. Summary of the Invention

[0003] The technical problem to be solved by the present invention is that the doping of some elements reduces the density of lithium titanium aluminum phosphate and its ionic conductivity. The present invention provides lithium calcium titanium aluminum phosphate, its preparation method and application.

[0004] To solve the above-mentioned technical problems, in a first aspect, this application provides a lithium calcium titanium aluminum phosphate, wherein the lithium calcium titanium aluminum phosphate has a chemical composition represented by the following general formula (1):

[0005] Li 1.3+x Al 0.3-x Ca x Ti 1.7 (PO4)3(1)

[0006] Where 0 < x < 0.2.

[0007] Preferably, 0 < x < 0.1.

[0008] Secondly, this application provides a method for preparing the aforementioned lithium calcium titanium aluminum phosphate, comprising the following steps:

[0009] According to the stoichiometric ratio in the general formula (1), lithium source, aluminum source, calcium source, titanium source and phosphorus source are wet ball-milled to obtain the precursor;

[0010] The precursor was sintered for the first time to obtain the crude product;

[0011] The crude product was post-treated, followed by a second sintering process to obtain product Li. 1.3+x Al 0.3- x Cax Ti 1.7 (PO4)3.

[0012] Preferably, the process of obtaining the precursor by wet ball milling of lithium source, aluminum source, calcium source, titanium source and phosphorus source includes the following steps:

[0013] The total material of lithium source, aluminum source, calcium source, titanium source and phosphorus source is added into a container containing wet ball milling media and ball milling beads for wet ball milling. After wet ball milling, the precursor is dried to obtain the precursor.

[0014] Preferably, the mass ratio of the total material to the milling beads is (0.4-0.5):1;

[0015] And / or, the wet ball milling media includes an alcohol solvent;

[0016] And / or, the grinding beads include zirconium beads.

[0017] Preferably, the first sintering of the precursor includes the following steps:

[0018] The precursor is first sintered in the first sintering stage, and then the second sintering stage is performed after the first sintering stage is completed.

[0019] The temperature of the first sintering stage is 300-400℃, and the time of the first sintering stage is 3-4 hours.

[0020] The temperature of the second sintering stage is 800-1000℃, and the time of the second sintering stage is 4-6 hours.

[0021] The heating rate during the first sintering stage is 4–5 °C / min;

[0022] The heating rate during the second sintering stage is 4–5 °C / min.

[0023] Preferably, the post-processing of the crude product includes the following steps:

[0024] The crude product is cooled and then compressed into tablets at a pressure of 400–850 MPa.

[0025] Preferably, the sintering temperature for the second sintering is 800–1000℃, and the sintering time for the second sintering is 3–4 hours.

[0026] The heating rate for the second sintering is 4–5 °C / min.

[0027] Preferably, the lithium source includes at least one of Li2CO3, LiOH·H2O, and Li2C2O4;

[0028] The aluminum source includes at least one of Al2O3, aluminum acetate nonahydrate, aluminum nitrate, aluminum phosphate, aluminum chloride, and aluminum hydroxide;

[0029] Calcium sources include Ca(OH)2;

[0030] The titanium source includes at least one of TiO2, tetrabutyl titanate, and titanium tetrachloride;

[0031] The phosphorus source includes at least one of NH4H2PO3, phosphoric acid, and ammonium hydrogen phosphate.

[0032] Secondly, this application provides an application of the above-described calcium titanium aluminum lithium phosphate or the calcium titanium aluminum lithium phosphate prepared by the above-described preparation method in lithium-ion batteries, lithium metal batteries, and solid-state batteries.

[0033] The lithium calcium titanium aluminum phosphate provided in this application has high density and high ionic conductivity. When applied to solid-state batteries, it serves as a solid electrolyte material with high density and ionic conductivity, increasing battery stability and improving battery electrical performance. Attached Figure Description

[0034] Figure 1 This is the EIS image of lithium calcium titanium aluminum phosphate prepared in Examples 1-8 of this application.

[0035] Figure 2 These are EIS diagrams of lithium calcium titanium aluminum phosphate prepared in Examples 9-18 and Comparative Examples 1-3 provided in this application. Detailed Implementation

[0036] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0037] This application provides a lithium calcium titanium aluminum phosphate, characterized in that the lithium calcium titanium aluminum phosphate has a chemical composition represented by the following general formula (1):

[0038] Li 1.3+x Al 0.3-x Ca x Ti 1.7 (PO4)3(1)

[0039] Where 0 < x < 0.2.

[0040] Specifically, x can be 0 < x < 0.1 or 0.1 ≤ x < 0.2.

[0041] The lithium calcium titanium aluminum phosphate provided in this application has high density and high ionic conductivity. When applied to solid-state batteries, it serves as a solid electrolyte material with high density and ionic conductivity, increasing battery stability and improving battery electrical performance.

[0042] In some embodiments, 0 < x < 0.1.

[0043] Specifically, when the calcium content x is in the range of 0 < x < 0.1, lithium calcium titanium aluminum phosphate has higher density and ionic conductivity. When used as a solid electrolyte material in batteries, it results in higher battery stability and is more conducive to improving battery performance.

[0044] Secondly, this application provides a method for preparing lithium calcium titanium aluminum phosphate, comprising the following steps:

[0045] According to the stoichiometric ratio in the general formula (1), lithium source, aluminum source, calcium source, titanium source and phosphorus source are wet ball-milled to obtain the precursor;

[0046] The precursor was sintered for the first time to obtain the crude product;

[0047] The crude product was post-treated, followed by a second sintering process to obtain product Li. 1.3+x Al 0.3- x Ca x Ti 1.7 (PO4)3.

[0048] Specifically, according to general formula (1) Li 1.3+x Al 0.3-x Ca x Ti 1.7 The stoichiometric ratio of (PO4)3 yields lithium, aluminum, calcium, titanium, and phosphorus sources. These sources are then subjected to wet ball milling. The wet ball milling media thoroughly wets the particle surface, improving milling efficiency and also facilitating a more thorough and uniform mixing of the lithium, aluminum, calcium, titanium, and phosphorus sources.

[0049] The crude product obtained from the first sintering has the chemical formula satisfying general formula (1) Li 1.3+x Al 0.3-x Ca x Ti 1.7 (PO4)3; A second sintering process is beneficial for forming a highly dense, high-conductivity product, Li. 1.3+x Al 0.3-x Ca x Ti 1.7 (PO4)3.

[0050] Compared with the prior art, the method for preparing lithium calcium titanium aluminum phosphate provided in this application obtains general formula (1) Li through a first sintering. 1.3+x Al 0.3-x Ca x Ti 1.7The crude (PO4)3 product was sintered a second time to obtain lithium calcium titanium aluminum phosphate with high density and high conductivity. The preparation method is simple.

[0051] In some embodiments, the process of wet ball milling lithium source, aluminum source, calcium source, titanium source and phosphorus source to obtain the precursor includes the following steps:

[0052] The total material of lithium source, aluminum source, calcium source, titanium source and phosphorus source is added into a container containing wet ball milling media and ball milling beads for wet ball milling. After wet ball milling, the precursor is dried to obtain the precursor.

[0053] Wet ball milling media are liquid, which can wet the particle surface, reduce the roughness of the particle surface, and further grind the particles, thereby improving ball milling efficiency.

[0054] After wet ball milling, the precursor is dried. Drying can be done by baking, where the slurry is directly dried and ground after ball milling. However, other methods, such as microwave drying, can also be used.

[0055] In some embodiments, the mass ratio of the total material to the milling beads is (0.4–0.5):1;

[0056] And / or, the wet ball milling media includes an alcohol solvent;

[0057] And / or, the grinding beads include zirconium beads.

[0058] Specifically, a total material to grinding ball mass ratio within the above range helps the grinding ball to grind particles.

[0059] The wet ball milling media includes an alcohol solvent, which may include ethanol, propanol, butanol, isobutanol, etc., with ethanol being the preferred alcohol solvent.

[0060] In some embodiments, the first sintering of the precursor includes the following steps:

[0061] The precursor is first sintered in the first sintering stage, and then the second sintering stage is performed after the first sintering stage is completed.

[0062] The temperature of the first sintering stage is 300-400℃, and the time of the first sintering stage is 3-4 hours.

[0063] The temperature of the second sintering stage is 800-1000℃, and the time of the second sintering stage is 4-6 hours.

[0064] The heating rate during the first sintering stage is 4–5 °C / min;

[0065] The heating rate during the second sintering stage is 4–5 °C / min.

[0066] Specifically, the first sintering process is divided into two stages. The first sintering stage is sintering at a low temperature, and the second sintering stage is sintering at a high temperature. This eases the internal tension in the molecular structure of the material, which helps to continuously increase the strength during the tempering stage, resulting in a more stable structure of the crude product.

[0067] In some preferred embodiments, the temperature of the first sintering stage is 300–400°C, and the time of the first sintering stage is 3–4 hours.

[0068] The temperature of the second sintering stage is 800-1000℃, and the time of the second sintering stage is 4-6 hours.

[0069] Specifically, the optimized conditions for the first and second sintering stages described above can yield a crude product with a more stable structure.

[0070] In some preferred embodiments, the temperature of the first sintering stage is 350°C and the time of the first sintering stage is 3 hours; after the first sintering stage is completed, the temperature is then raised to carry out the second sintering stage, the temperature of the second sintering stage is 850°C and the time of the second sintering stage is 5 hours.

[0071] The heating rate for both the first and second sintering stages is 5℃ / min.

[0072] In some embodiments, post-processing of the crude product includes the following steps:

[0073] The crude product is cooled and then compressed into tablets at a pressure of 400–850 MPa.

[0074] Specifically, cooling the crude product means cooling it to room temperature. The cooling method can be natural cooling or cooling in a cold water environment.

[0075] If the pressing pressure is too low, ceramic sheets of a certain particle size cannot be obtained, which is not conducive to sufficient secondary sintering; if the pressing pressure is too high, the preparation cost will increase.

[0076] After cooling, the crude product is compressed into tablets using a tablet press to obtain ceramic tablets with a particle size of 2–5 μm. The increased surface area facilitates a more thorough second sintering process.

[0077] In some embodiments, the sintering temperature of the second sintering is 800–1000°C, and the sintering time of the second sintering is 3–4 hours.

[0078] The heating rate for the second sintering is 4–5 °C / min.

[0079] Specifically, performing a second sintering within the aforementioned range helps to obtain lithium calcium titanium aluminum phosphate with high density and high ionic conductivity. If the second sintering temperature is too low, it is impossible to obtain lithium calcium titanium aluminum phosphate with high density and high ionic conductivity. If the second sintering temperature is too high, the crude product will oxidize, and the impurity content will increase.

[0080] In some preferred embodiments, the sintering temperature of the second sintering is 900°C, and the sintering time of the second sintering is 5 hours;

[0081] The heating rate for the second sintering is 5℃ / min.

[0082] In some embodiments, the lithium source includes at least one of Li2CO3, LiOH·H2O, and Li2C2O4.

[0083] In some embodiments, the aluminum source includes at least one of Al2O3, aluminum acetate nonahydrate, aluminum nitrate, aluminum phosphate, aluminum chloride, and aluminum hydroxide.

[0084] In some embodiments, the calcium source includes Ca(OH)2.

[0085] In some embodiments, the titanium source includes at least one of TiO2, tetrabutyl titanate, and titanium tetrachloride.

[0086] In some embodiments, the phosphorus source includes at least one of NH4H2PO3, phosphoric acid, and ammonium hydrogen phosphate.

[0087] Thirdly, this application provides an application of lithium calcium titanium aluminum phosphate prepared by the above-described method in lithium-ion batteries, lithium metal batteries, and solid-state batteries.

[0088] Specifically, the Li shown in general formula (1) provided in this application 1.3+x Al 0.3-x Ca x Ti 1.7 Lithium calcium titanium aluminum phosphate (PO4)3, or lithium calcium titanium aluminum phosphate prepared by the above-described method, can be used as an ion conductor in lithium-ion batteries and lithium metal batteries, or as a solid electrolyte material in solid-state batteries.

[0089] The present invention will be further illustrated by the following examples.

[0090] Specifically, this invention discloses lithium calcium titanium aluminum phosphate and its preparation method, the preparation method of which includes the following steps:

[0091] Example 1

[0092] Based on the fact that x is 0.05 in general formula (1), the chemical formula of lithium calcium titanium aluminum phosphate is Li 1.35 Al 0.25 Ca 0.05 Ti 1.7 (PO4)3, according to Li 1.35 Al 0.25 Ca 0.05 Ti 1.7 The stoichiometric ratio of LiOH·H2O, Al2O3, TiO2, Ca(OH)2, and NH4H2PO3 for (PO4)3 was determined by weighing out the total material. This total material was then added to a planetary ball mill containing wet milling media (ethanol) and zirconium grinding beads, and milled. After milling, the slurry was dried and ground to obtain the precursor. The mass ratio of the total material to the grinding beads was 0.45:1.

[0093] The precursor was subjected to a first sintering in a muffle furnace. The first sintering procedure consisted of a first sintering stage followed by a second sintering stage. The sintering temperature for the first sintering stage was 350℃, and the sintering time was 3 hours. The sintering temperature for the second sintering stage was 850℃, and the sintering time was 5 hours. The heating rate for both the first and second sintering stages was 5℃ / min. A crude product was obtained after the first sintering.

[0094] The crude product was naturally cooled to room temperature and then pressed into sheets at a pressure of 850 MPa to obtain ceramic sheets with a diameter of 2–5 μm. These sheets were then subjected to a second sintering process in a muffle furnace at 900 °C for 5 hours at a heating rate of 5 °C / min. After the second sintering, the sheets were naturally cooled to room temperature to obtain a highly dense and electrically conductive product, Li. 1.35 Al 0.25 Ca 0.05 Ti 1.7 (PO4)3.

[0095] Example 2

[0096] Example 2 is the same as Example 1 in most steps, except that the tableting pressure is different. The tableting pressure is 700 MPa, and the rest is the same as Example 1.

[0097] Example 3

[0098] Example 3 is the same as Example 2 in most steps, except that the second sintering temperature is different. The second sintering temperature is 850°C. The rest is the same as Example 2.

[0099] Example 4

[0100] Example 4 is the same as Example 2 in most steps, except that the second sintering temperature is different. The second sintering temperature is 800°C. The rest is the same as Example 2.

[0101] Example 5

[0102] Example 5 is the same as Example 1 in most steps, except that the tableting pressure is different. The tableting pressure is 550 MPa, and the rest is the same as Example 1.

[0103] Example 6

[0104] Example 6 is the same as Example 1 in most steps, except that the tableting pressure is different. The tableting pressure is 400 MPa, and the rest is the same as Example 1.

[0105] Example 7

[0106] Example 7 is the same as Example 2 in most steps, except that the second sintering temperature is different. The second sintering temperature is 1000℃, and the rest is the same as Example 2.

[0107] Example 8

[0108] Example 8 is the same as Example 2 in most steps, except that the second sintering temperature is different. The second sintering temperature is 1100℃, and the rest is the same as Example 2.

[0109] Example 9

[0110] Example 9 is the same as Example 2 in most steps, except that the second sintering temperature is different. The second sintering temperature is 700°C. The rest is the same as Example 2.

[0111] Example 10

[0112] Example 10 is the same as Example 1 in most steps, except that x in general formula (1) is 0.07; the rest of the preparation method is the same as Example 1.

[0113] Example 11

[0114] Example 11 is the same as Example 1 in most steps, except that x in general formula (1) is 0.1; the rest of the preparation method is the same as Example 1.

[0115] Example 12

[0116] Example 12 is largely the same as Example 2, except that the first sintering procedure is different in Example 12. Example 12 does not have a first sintering stage or a second sintering stage. The precursor is sintered for the first time in a muffle furnace at a temperature of 850°C for 8 hours. After the first sintering, a crude product is obtained. The rest is the same as in Example 1.

[0117] Example 13

[0118] Example 13 is largely the same as Example 2, except that the temperatures and times of the first and second sintering stages are different. Specifically, the sintering temperature of the first sintering stage is 300°C and the sintering time is 4 hours; the sintering temperature of the second sintering stage is 800°C and the sintering time is 4 hours. The rest is the same as Example 2.

[0119] Example 14

[0120] Example 14 is largely the same as Example 2, except that the temperatures and times of the first and second sintering stages are different. Specifically, the sintering temperature of the first sintering stage is 300°C and the sintering time is 4 hours; the sintering temperature of the second sintering stage is 900°C and the sintering time is 4 hours. The rest is the same as Example 2.

[0121] Example 15

[0122] Example 15 is the same as Example 1 in most steps, except that the tableting pressure is different. The tableting pressure is 625 MPa, and the rest is the same as Example 1.

[0123] Example 16

[0124] Example 16 is largely the same as Example 2, except that the temperatures and times of the first and second sintering stages are different. Specifically, the sintering temperature of the first sintering stage is 200°C and the sintering time is 4 hours; the sintering temperature of the second sintering stage is 700°C and the sintering time is 4 hours. The rest is the same as Example 2.

[0125] Example 17

[0126] Example 17 is largely the same as Example 2, except that the temperatures and times of the first and second sintering stages are different. Specifically, the sintering temperature of the first sintering stage is 500°C and the sintering time is 4 hours; the sintering temperature of the second sintering stage is 1100°C and the sintering time is 5 hours. The rest is the same as Example 2.

[0127] Example 18

[0128] Example 18 is the same as Example 1 in most steps, except that x in general formula (1) is 0.18; the rest of the preparation method is the same as Example 1.

[0129] Comparative Example 1

[0130] Comparative Example 1 is the same as Example 1 in most steps, except that x in general formula (1) is 0, and there is no calcium doping; no Ca(OH)2 is added when preparing the precursor, and the rest of the preparation method is the same as in Example 1.

[0131] Comparative Example 2

[0132] Comparative Example 2 is the same as Example 1 in most steps, except that x in general formula (1) is 0.3 and the calcium content of the doped calcium is higher; the rest of the preparation method is the same as Example 1.

[0133] Comparative Example 3

[0134] Comparative Example 3 is the same as Example 1 in most steps, except that x in general formula (1) is 0.2 and the calcium content of the doped calcium is higher; the rest of the preparation method is the same as Example 1.

[0135] The products prepared in the above embodiments and comparative examples were subjected to EIS testing and density testing.

[0136] EIS Testing Methods

[0137] Using a Solartron 1260A+1470E electrochemical workstation, gold was deposited on both sides of a ceramic substrate using an ion sputtering apparatus. EIS testing was then performed using the electrochemical workstation, with a frequency range of 10 Hz. 6 Between Hz and 1Hz.

[0138] Density testing methods

[0139] Using Archimedes' method, the actual density of the electrolyte ceramic sheet is obtained by dividing the dry weight of the electrolyte ceramic sheet by its total volume. The formula for calculating the actual density is as follows:

[0140]

[0141] Where M0 represents the dry weight of the tested solid electrolyte ceramic sheet;

[0142] M1 represents the mass of the tested solid electrolyte ceramic sheet in ethanol;

[0143] ρ 乙醇 This indicates the density of ethanol at the test temperature;

[0144] ρ 空气 This indicates the density of air at the test temperature.

[0145] The formula for calculating the density of the product is as follows:

[0146]

[0147] The product's density is ρ 实际 The actual density divided by the theoretical density of the material.

[0148] The test results are shown in Table 1.

[0149] Table 1

[0150]

[0151]

[0152] pass Figure 1 , 2 As shown in Table 1, compared with Examples 1, 10-11 and Comparative Examples 1-3, the calcium titanium aluminum phosphate in Comparative Example 1 has low density and low conductivity due to the absence of calcium metal doping. With the addition of calcium metal doping, the density and conductivity of calcium titanium aluminum phosphate first increase and then decrease in the range of 0 < x < 0.2 as x increases. The calcium titanium aluminum phosphate prepared in the range of 0 < x < 0.1 has higher density and conductivity. When x ≥ 0.2, the density and conductivity of calcium titanium aluminum phosphate are low.

[0153] Comparing Examples 1, 2, 5, 15, and Example 6, when the pressing pressure is below 550 MPa, the density and conductivity of the prepared calcium titanium aluminum phosphate are lower. When the pressing pressure is in the range of 550–850 MPa, the density and conductivity of the prepared calcium titanium aluminum phosphate are higher. Comparing Examples 1, 3, 4, 7, and Examples 8, 9, when the second sintering temperature is outside the 800–1000 °C range of this application, the density and conductivity of the calcium titanium aluminum phosphate are lower. When the second sintering temperature is within the 800–1000 °C range of this application, the density and conductivity of the calcium titanium aluminum phosphate are higher.

[0154] Comparing Examples 1 and 12, Example 12 lacked a first and second sintering stages in its first sintering, resulting in low density and electrical conductivity of the prepared calcium titanium aluminum phosphate. This indicates that a staged sintering method in the first sintering helps improve the density and electrical conductivity of calcium titanium aluminum phosphate, leading to a more stable structure. Comparing Examples 1, 13-14 and Examples 12, 16-17, the sintering temperatures in the first and second sintering stages of Examples 16-17 did not meet the requirements of the first sintering stage temperature range of 300–400°C and the second sintering stage temperature range of 800–1000°C as per this application. The resulting calcium titanium aluminum phosphate exhibited lower density and electrical conductivity. This demonstrates that a staged sintering method in the first sintering, with temperatures in the first sintering stage range of 300–400°C and the second sintering stage range of 800–1000°C, helps to form calcium titanium aluminum phosphate with a stable structure and high density and electrical conductivity.

[0155] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A lithium calcium titanium aluminum phosphate, characterized in that, The lithium calcium titanium aluminum phosphate has the following chemical composition represented by the general formula (1): Li 1.3+x Al 0.3-x Ca x You 1.7 (PO4)3(1) Where 0 < x < 0.

2.

2. The lithium calcium titanium aluminum phosphate according to claim 1, characterized in that, 0<x<0.1。 3. A method for preparing lithium calcium titanium aluminum phosphate according to any one of claims 1-2, characterized in that, Includes the following steps: According to the stoichiometric ratio in the general formula (1), lithium source, aluminum source, calcium source, titanium source and phosphorus source are wet ball-milled to obtain the precursor; The precursor was sintered for the first time to obtain the crude product; The crude product was post-treated, followed by a second sintering process to obtain product Li. 1.3+x Al 0.3-x Ca x Ti 1.7 (PO4)3.

4. The method for preparing lithium calcium titanium aluminum phosphate according to claim 3, characterized in that, The process of wet ball milling lithium, aluminum, calcium, titanium, and phosphorus sources to obtain precursors includes the following steps: The total material of lithium source, aluminum source, calcium source, titanium source and phosphorus source is added into a container containing wet ball milling media and ball milling beads for wet ball milling. After wet ball milling, the precursor is dried to obtain the precursor.

5. The method for preparing lithium calcium titanium aluminum phosphate according to claim 4, characterized in that, The mass ratio of the total material to the milling beads is (0.4-0.5):1; And / or, the wet ball milling media includes an alcohol solvent; And / or, the grinding beads include zirconium beads.

6. The method for preparing lithium calcium titanium aluminum phosphate according to claim 3, characterized in that, The first sintering of the precursor includes the following steps. The precursor is first sintered in the first sintering stage, and then the second sintering stage is performed after the first sintering stage is completed. The temperature of the first sintering stage is 300-400℃, and the time of the first sintering stage is 3-4 hours. The temperature of the second sintering stage is 800-1000℃, and the time of the second sintering stage is 4-6 hours. The heating rate during the first sintering stage is 4–5 °C / min; The heating rate during the second sintering stage is 4–5 °C / min.

7. The method for preparing lithium calcium titanium aluminum phosphate according to claim 3, characterized in that, The post-processing of the crude product includes the following steps: The crude product is cooled and then compressed into tablets at a pressure of 400–850 MPa.

8. The method for preparing lithium calcium titanium aluminum phosphate according to claim 3, characterized in that, The sintering temperature for the second sintering is 800–1000℃, and the sintering time for the second sintering is 3–4 hours. The heating rate for the second sintering is 4–5 °C / min.

9. The method for preparing lithium calcium titanium aluminum phosphate according to claim 3, characterized in that, The lithium source includes at least one of Li2CO3, LiOH·H2O, and Li2C2O4; The aluminum source includes at least one of Al2O3, aluminum acetate nonahydrate, aluminum nitrate, aluminum phosphate, aluminum chloride, and aluminum hydroxide; Calcium sources include Ca(OH)2; The titanium source includes at least one of TiO2, tetrabutyl titanate, and titanium tetrachloride; The phosphorus source includes at least one of NH4H2PO3, phosphoric acid, and ammonium hydrogen phosphate.

10. The application of lithium calcium titanium aluminum phosphate prepared by any one of claims 1-2 or any one of claims 3-9 in lithium-ion batteries, lithium metal batteries, and solid-state batteries.